Co-Occurrence of Autism Spectrum Disorder and Achondroplasia - Dy, Angel Belle Cheng; Tanchanco, Lourdes Sumpaico (Frontiers in Psychiatry, 2019)
Autism spectrum disorder (ASD) and achondroplasia are common disorders on their own. However, this case of co-occurrence in the same patient has not yet been reported in literature except for a hypothesized statistical probability based on prevalence studies stating that 2-5 in 10 million children could have the probability of having both conditions occur simultaneously. Achondroplasia typically presents with motor delays and difficulties that are related to musculoskeletal impairments that can affect self-care, mobility and social cognition, however the presence of delays in other domains of development, particularly in social communication, raises a suspicion of a co-occurring autism spectrum disorder. The content of this report reviews the common delays and difficulties seen in children with achondroplasia and those with autism spectrum disorder, and describes the presence of both in the child presented in this case.